МАДАНИЯТЛАРАРО МУЛОҚОТДА ФРАЗЕОЛОГИЗМЛАРНИНГ ЎРНИ ҲАҚИДА - Худайбергенов, А.А. (SCIENCE and SOCIETY, 2024)
In this article analyzes the role of phraseologisms in intercultural communication and the features of anthropocentric principles in studying the picture of the world from a linguistic point of view and the definition of the concept of intercultural communication and the opinions expressed by world linguists regarding the field of phraseology.